Serum YKL-40 levels in patients with multiple sclerosis - Ahmet Dönder; Hasan Hüseyin Özdemir (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Multiple sclerosis (MS) is a chronic inflammatory disease affecting the central nervous system. The YKL-40 protein, which is secreted from various cells that contribute to inflammation and infection, plays a role in immune regulation. Objective: This study investigated the serum YKL-40 levels of patients with clinically isolated syndrome (CIS) and MS. Methods: The participants was divided into three groups: 1) patients with CIS (n = 20); 2) patients with relapsing-remitting MS (RRMS; n = 39); and 3) healthy individuals (n = 35). The YKL-40 levels in serum samples obtained from the participants were measured using enzyme-linked immunoassays. Results: The median serum YKL-40 level was 20.2 ng/mL (range 9.8-75.9 ng/mL) in the patients with CIS, 22.7 ng/mL (range 13.4-57.9 ng/mL) in the patients with RRMS and 11.0 ng/mL (range 10.0-17.3 ng/mL) in the control group (p < 0.001). The serum YKL-40 levels in the patients with RRMS were correlated with the patients’ expanded disability status scale scores and ages (p < 0.05). No relationships were determined between the serum YKL-40 levels and the other variables (p > 0.05). The serum YKL-40 levels were higher in the CIS group than in the MS group. These findings show that the serum YKL-40 levels were high even at the beginning of the disease. The serum YKL-40 levels were also not involved in the progression to clinically definite MS. Conclusions: The findings from this study suggested that YKL-40 may be a useful marker for the inflammatory process of MS.